Arabic tweeps dialect prediction based on machine learning approach - Khaled Alrifai; Ghaida Rebdawi; Nada Ghneim (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this paper, we present our approach for profiling Arabic authors on twitter, based on their tweets. We consider here the dialect of an Arabic author as an important trait to be predicted. For this purpose, many indicators, feature vectors and machine learning-based classifiers were implemented. The results of these classifiers were compared to find out the best dialect prediction model. The best dialect prediction model was obtained using random forest classifier with full forms and their stems as feature vector.